2016
DOI: 10.1016/j.ijsu.2015.12.071
|View full text |Cite
|
Sign up to set email alerts
|

High patency of proximal splenorenal shunt: A myth or reality ? – A prospective cohort study

Abstract: Dynamic CT portography is useful for evaluation of shunt patency. Proximal splenorenal shunts have a high blockage rate which has hitherto not been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…The overall patency of PSRS is reported between 60-90% and the majority of shunt thrombosis occurs after a few months 5 , 6 . After a thorough search of the literature, we could find only one case of in-hospital, radiologically documented shunt thrombosis presenting as re-bleed within 48 hours which was managed conservatively 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall patency of PSRS is reported between 60-90% and the majority of shunt thrombosis occurs after a few months 5 , 6 . After a thorough search of the literature, we could find only one case of in-hospital, radiologically documented shunt thrombosis presenting as re-bleed within 48 hours which was managed conservatively 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Одним из основных факторов, ограничивающих применение метода у пациентов с ПГ, зачастую является недостаточный диаметр сосуда, не позволяющий обеспечить адекватный отток из воротной системы и сформировать анастомоз, который также должен иметь достаточный диаметр (минимум 8 мм) [1,2,27,28,34,35]. К сожалению, лишь у небольшого числа пациентов с ПГ левая желудочная вена расширяется до приемлемых для хирургического шунтирования размеров [32][33].…”
Section: а бunclassified
“…Диаметр самого анастомоза составил в среднем 11,03 и 10,63 см соответственно (р = 0,265). Следует отметить, что отсутствие влияния размера шунта на его функцию обусловлено тем, что у всех 50 пациентов изначально был сформирован анастомоз адекватного диаметра (от 8 до 14 мм) [35].…”
Section: а бunclassified
“…The beneficial effects of shunt surgery are mitigated when shunt get blocked. Mishra et al10 reported that 25% (3/12) of NCPF patients developed the shunt blockage during follow up. In present study shunt blockage rate was 1/16 (6.25%), the low rate may be due to the fact that we did not used CT portography routinely in all patients on follow up to assess shunt patency.Splenectomy alone is considered as sub-optimal treatment in NCPF, post splenectomy increase risk of thrombosis of spleno-portal venous axis is there and it can result in increased risk of PHTN related bleed.…”
mentioning
confidence: 99%